On the flowering behaviour of the rice crop at the Crop weather stations in India - VENKATARAMAN , S.; NARASIMHAMURTHY, K. (MAUSAM, 1973)
The need for evaluating the type of flowering behaviour of a rice crop for understanding its weather relationship is outlined. An examination of the duration of the vegetative phase on extreme sowing dates (i) at a number of stations for early Kharif crop and (ii) at south Peninsular stations for late Kharif crop, is made, to screen varieties for presence or absence of photoperiodic response. The likely alternate flowering month for the photosensitive varieties is indicated.